Dynamic performance of sandwich composite plates with circular hole/cut-out: A mixed experimental–numerical study. (1st November 2015) - Mondal, S.; Patra, A.K.; Chakraborty, S.; Mitra, N.
Abstract: The dynamic characteristics of sandwich composite plates with holes at various locations are investigated both experimentally and through numerical simulations. The critical parameters which affect the natural frequencies of such plates with holes or cut-outs are the core and face sheet thicknesses, diameter and location of the holes and aspect ratio of the plate. A rigorous parametric study has been conducted to determine their interrelationship and presented in a concise manner. An experimental investigation has been conducted in the beginning to get an idea about the variations of the above mentioned parameters. The results can be utilized to determine the changes in dynamic characteristics of sandwich composite plates with holes with specified diameters and locations. The methodology can also be useful to control the dynamic responses of such plates by incorporating holes of chosen diameters at appropriate locations. The results may be used to create design curves for satisfactory dynamic performances of sandwich composite plate with holes.